Systematic Literature Review (SLR): Related to Education Level and Work Environment on Work Performance in Institutions - Gian Hiwono, Patrik Sixdio (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the influence of education level, work environment, and work experience on work performance. Through a systematic literature review, the study found that all three factors significantly affect work performance, albeit with different complexities and nuances. The level of education, both formal and non-formal, provides an important cognitive foundation and practical skills, but its relevance varies depending on the individual's employment context and demographics. The work environment, with its physical and non-physical dimensions, creates conditions that support or hinder productivity, in which organizational structure, culture, and relationships between employees play a key role. The psychosocial environment, including job satisfaction, support, and stress management, has also proven crucial in influencing employee well-being and performance. Work experience, with its accumulation of knowledge and practical expertise, is a strong predictor of performance, especially in complex jobs. Therefore, organizations need to consider the complex interactions between these factors in designing effective human resource development policies. Further research is needed to explore the contextual factors that moderate these relationships and develop a more comprehensive model to improve work performance.